Perancangan Sistem Penilaian Performansi Karyawan - Pratiwi, Loren; Sitorus, Hotna Marina; Marthalia, Elizabeth (Jurnal Rekayasa Sistem Industri, 2016)
Company X is one of the bakery companies that has several branch shops in Bandung. Over thepast few years, the performance of its human resource was stagnant and undeveloped. Especially in theposition of cashiers and salespersons who serve the consumers. Without a good human resource performancemanagement, Company X will not be able to survive in the competition. One of the requirements of goodhuman resource management performance is a good performance appraisal system. Performance assessmentconducted by Company X is still generic, and involving the assessment criteria that are very common.Besides, this assessment is also used to measure all positions in the company. Sometimes, the assessmentprocess was very subjective, which often causes employees with different performance get the same value.This research aims to design a performance appraisal system for the position of cashier and salesperson atCompany X by using Behaviorally Anchored Rating Scales (BARS). A performance appraisal system wasdesign started from the identification of assessment criteria and the determination of the scale of assessmentstandards, and ends with a form design and assessment procedures. The study also designed a feedbacksystem, in order to improve the performance of the cashiers and salespersons at Company X. The developedassessment system then tested in Company X to see how well the assessment able to distinguish employeesperformance, where employees with different performance obtain different values. Besides these trials alsoaccomplished the objective of the proposed system, where the same employees have the same value relativelydespite assessed by different people.